Long‐Term Risk Stratification of Patients Undergoing Coronary Angiography According to the Thrombolysis in Myocardial Infarction Risk Score for Secondary Prevention. Issue 14 (16th July 2019) - Zafrir, Barak; Adawi, Salim; Khalaily, Marah; Jaffe, Ronen; Eitan, Amnon; Barnett‐Griness, Ofra; Saliba, Walid
Abstract : Background: A risk score for secondary prevention after myocardial infarction (Thrombolysis in Myocardial Infarction Risk Score for Secondary Prevention [TRS2P]), based on 9 established clinical factors, was recently developed from the TRA2°P‐TIMI50 (Thrombin Receptor Antagonist in Secondary Prevention of Atherothrombotic Ischemic Events) trial. We aimed to evaluate the performance of TRS2P for predicting long‐term outcomes in real‐world patients presenting for coronary angiography. Methods and Results: A retrospective analysis of 13 593 patients referred to angiography for the assessment or treatment of coronary disease was performed. Risk stratification for 10‐year major adverse cardiovascular events was performed using the TRS2P, divided into 6 categories (0 to ≥5 points), and in relation to the presenting coronary syndrome. All clinical variables, except prior coronary artery bypass grafting, were independent risk predictors. The annualized incidence rate of major adverse cardiovascular events increased in a graded manner with increasing TRS2P, ranging from 1.65 to 16.6 per 100 person‐years ( P trend <0.001). Compared with the lowest‐risk group (risk indicators=0), the hazard ratios (95% CIs) for 10‐year major adverse cardiovascular events were 1.60 (95% CI, 1.36–1.89), 2.58 (95% CI, 2.21–3.02), 4.31 (95% CI, 3.69–5.05), 6.43 (95% CI, 5.47–7.56), and 10.03 (95% CI, 8.52–11.81), in those with 1, 2, 3, 4 and ≥5 risk indicators, respectively. Risk gradation was consistent among individual clinical end points. TRS2P showed reasonable discrimination with C‐statistics of 0.693 for major adverse cardiovascular events and 0.758 for mortality. The graded relationship between the risk score and event rates was observed in both patients presenting with acute and nonacute coronary syndromes. Conclusions: The use of TRS2P, a simple risk score based on routinely collected variables, enables risk stratification in patients undergoing coronary angiography. Its predictive value was demonstrated in a real‐world setting with long‐term follow‐up and regardless of the acuity of coronary presentation.